CELL EXPANSION-DEPENDENT INFLAMMATORY AND METABOLIC PROFILE OF HUMAN BONE MARROW MESENCHYMAL STEM CELLS - PATRICIA PRIETO; MARÍA FERNÁNDEZ-VELASCO; MARIA EUGENIA FERNÁNDEZ-SANTOS; PEDRO LUIS SÁNCHEZ; VERÓNICA TERRÓN; PALOMA MARTIN-SANZ; FRANCISCO FERNÁNDEZ-AVILÉS; LISARDO BOSCÁ (Frontiers in Physiology, 2016)
Stem cell therapy has emerged as a promising new area in regenerative medicine allowing the recovery of viable tissues. Among the many sources of adult stem cells, bone marrow-derived are easy to expand in culture via plastic adherence and their multipotentiality for differentiation make them ideal for clinical applications. Interestingly, several studies have indicated that MSCs expansion in vitro may be limited mainly due to cell aging related to the number of cell divisions in culture. We have determined that MSCs exhibit a progressive decline across successive passages in the expression of stem cell markers, in plasticity and in the inflammatory response, presenting low immunogenicity. We have exposed human MSCs after several passages to TLRs ligands and analyzed their inflammatory response. These cells responded to pro-inflammatory stimuli (i.e., NOS-2 expression) and to anti-inflammatory cytokines (i.e., HO1 and Arg1) until two expansions, rapidly declining upon subculture. Moreover, in the first passages, MSCs were capable to release IL1β, IL6 and IL8, as well as to produce active MMPs allowing them to migrate. Interestingly enough, after two passages, anaerobic glycolysis was enhanced releasing high levels of lactate to the extracellular medium. All these results may have important implications for the safety and efficacy of MSCs-based cell therapies.